Lead poisoning and marginalization in newborns of Morelos, Mexico - Martha María Téllez-Rojo; Luis F Bautista-Arredondo; Vesta Richardson; Daniel Estrada-Sánchez; Laura Ávila-Jiménez; Camilo Ríos; Alejandra Cantoral-Preciado; Martín Romero-Martínez; Delia Flores-Pimentel; Maria del Carmen Melo-Zurita; Anita Romero-Ramírez; Marco Antonio León-Mazón; et al. (Instituto Nacional de Salud Pública, 2017)
Objective. To determine the prevalence of lead (Pb) poi- soning at birth in Morelos, analyze its distribution by social marginalization level, and estimate the association with the use of lead glazed ceramics (LGC). Materials and methods. Blood lead level (BLL) in umbilical cord was measured in a representative sample of 300 randomly selected births at the Morelos Health Services and state IMSS. Results. The prevalence of Pb poisoning at birth (BLL> 5µg/dL) was 14.7%(95%CI: 11.1, 19.3) and 22.2% (95%CI: 14.4, 32.5) in the most socially marginalized municipalities. 57.1% (95%CI: 51.3, 62.7)of the mothers used LGC during pregnancy, and the frequency of use was significantly associated with BLL. Conclusion. This is the first study to document the proportion of new- borns with Pb poisoning who are at risk of experiencing the related adverse effects. It is recommended to monitor BLL at birth and take action to reduce this exposure, especially in socially marginalized populations.